Parasitic leiomyoma in the vagina - Abd. Wahab, Noraziana; Awang, Mokhtar; Harun, Norra (Faculty of Medicine, International Islamic University Malaysia, 2008)
Parasitic leiomyoma is the rarest type of leiomyoma and develop when a leiomyoma attaches itself to another organ. Vaginal leiomyomas usually arise from anterior vaginal wall. We report a case of parasitic leiomyoma in the vagina together with uterine leiomyoma in a 48 year old lady presented with palpable mass perabdomen and anaemic symptoms. The size and location of the tumours necessitated abdominal and vaginal approach for better surgical access.